Improving the properties of reclaimed waste tire rubber by blending with poly(ethylene-co-vinyl acetate) and electron beam irradiation - Ramarad, Suganti (2016)
Non-degradable waste tire generation around the world is growing at an alarming rate. Diversifying the recycling route of these waste tires is essential to solve the problem. One way is to incorporate them into polymers and convert them into new products. However, incorporation of ground tire rubber into thermoplastics has been hampered due to lack of toughness and adhesion between phases. To address the issue, this study utilized reclaimed waste tire rubber (RTR) instead; and evaluated the properties of RTR and poly(ethylene-co-vinyl acetate) (EVA) blends. The properties of the RTR/EVA blends were further enhanced by compatibilization and electron beam irradiation.